Optimal portfolio allocation with real assets : a Finnish perspective - Parviainen, Teemu (2017)
Alternative market assets, i.e. those which are not part of the ''traditional'' financial assets, have become increasingly popular globally during the last decade. The purpose of this study is to examine the potential benefits of including real investment assets, specifically timberland and real estate holdings, for a investor investing to either domestic or international markets. Specifically the questions to be asked are: Do Finnish real investment assets offer diversification benefits in respect of increased risk-adjusted returns? What are the optimal asset allocations? The analyzed time-series for alternative investments represent quarterly total returns of average Finnish timberland and nonsubsidized housing assets during the period of 1987/Q1-2014/Q4. The problem will be approached by the means of portfolio diversification theory utilizing both static and dynamic backtesting optimization frameworks to determine the VaR- and CVaR-efficient allocations. The results indicate, that the benefits of allocating wealth into real investment assets may differ markedly. While for all-domestic portfolio the efficient frontier does not markedly shift, for internationally diversified portfolio efficient frontiers are greatly enhanced in terms of risk-return characteristics, when real estate and timber assets are included. Dynamic optimization routine reveals that the optimal allocations are clearly time-dependent and especially the weight of timber tends to be negatively affected by financial and economic crisis periods. However, the implied risk-reduction contributions indicate that both timber and real estate assets are able to lower the overall riskiness of investment portfolio also throughout these crisis periods. The optimal weight of real estate is rather persistent, often being over 50 % in both portfolios, apart from the early 1990s. Therefore, it can be concluded that the studied real investment assets have great potential to enhance the risk-return characteristics of risky portfolios.